Pelatihan Bantuan Hidup Dasar (BHD) Kepada Masyarakat Awam di Desa Pajala Kabupaten Muna Barat Provinsi Sulawesi Tenggara - Ardan, Achmad; Sukmaningtyas, Wilis; Susanto, Amin (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Background. Basic life support is a basic aspect of rescue action in relation to cardiac arrest. To support the success and quality of life of patients, important aspects include prevention of cardiac arrest, early cardiopulmonary resuscitation (CPR)/cardiopulmonary resuscitation (CPR), activation of the emergency response system, effective advanced life support, and integrated post-cardiac arrest management. The purpose of this community service activity is to provide basic life support training to the general public so that they can provide assistance when an emergency arises. This PKM method is carried out with the practice of Basic Life Support Training. The results of this community service obtained data on the characteristics of participants dominated by men, namely 18 participants (60%), while for participants with female gender there were 12 respondents (40%). The characteristics of education obtained data that the high school education history was 16 participants (53%), for the characteristics of employment status, data obtained that it was dominated by farmers as many as 16 participants (54%). The level of BHD implementation with a good category is 20 respondents (67%), while for the less category level is 10 respondents (33%). The output produced is in the form of leaflets and scientific publications. This PKM activity is expected to fulfill the author’s final assignment in taking the Anesthesiology Nursing Study Program at Harapan Bangsa University, Purwokerto.